Millimeterwellen On-Chip Antennensysteme für die Integration in SoC Applikationen - Göttel, Benjamin (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2017)
In this work antenna systems for radar- and communication systems are presented. Additionally, a QFN-based packaging concept is evaluated. For communication systems the antenna systems are optimized for maximum radiated power to extend the transmit range. Therefore, a new concept for the power-combination of parallelized amplifiers is presented, where the signals of the amplifiers are combined in a single antenna element.